2013
DOI: 10.1179/1743132812y.0000000135
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 and caspase-8 trigger caspase-3 activation following 6-OHDA-induced stress in human dopaminergic neurons differentiated from ReNVM stem cells

Abstract: The study showed that 6OHD-induced toxicity triggered caspase mediated death of dDCN. This finding is in support of previous studies using different PD model showing that 6OHD can induce caspases-2 and -3 activation through apoptotic pathway and that both caspases can activate caspase-3 in PD. In addition, our results suggest that caspase-2 cause's cell death might be via an indirect NF kappaB route. This study has established a PD model which can provide better insight to PD pathogenesis on a biochemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The cells were maintained in ReNcell NSC maintenance medium [SCM005; Chemicon (Millipore), Watford, UK] and were differentiated into dopaminergic neurons (dDCN), as described previously [12]. To ensure that the dDCN were indeed dopaminergic neurons, the dopamine marker tyrosine hydroxylase was used and the cells were treated with 100 mM 6-OHDA for 2 h to induce stress, please see our recently published article for details [12], after which fresh media were replaced and cells were either collected immediately termed as 0 h, or left in the incubator at 371C and collected after 24 and 72 h. The untreated group was subjected to media change only and was collected at 0 h, termed as control.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The cells were maintained in ReNcell NSC maintenance medium [SCM005; Chemicon (Millipore), Watford, UK] and were differentiated into dopaminergic neurons (dDCN), as described previously [12]. To ensure that the dDCN were indeed dopaminergic neurons, the dopamine marker tyrosine hydroxylase was used and the cells were treated with 100 mM 6-OHDA for 2 h to induce stress, please see our recently published article for details [12], after which fresh media were replaced and cells were either collected immediately termed as 0 h, or left in the incubator at 371C and collected after 24 and 72 h. The untreated group was subjected to media change only and was collected at 0 h, termed as control.…”
Section: Cell Culturementioning
confidence: 99%
“…Recently, we and others have shown that ReNVM can be differentiated successfully into DCN (dDCN) and provide a suitable model to study Parkinson's disease pathogenesis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We chose the immortalized hNPC cell line ReNcell VM (ReN) as a base for our platform because the cells can be maintained for more than 45 passages, are commercially available, and can differentiate into neurons and glial cells with simple growth-factor deprivation 1527 . The ReN cells were then transfected with IRES-mediated polycistronic lentiviral vectors containing FAD genes encoding human APP with both K670N/M671L (Swedish) and V717I (London) mutations (APPSL), PSEN1 with ΔE9 mutation (PSEN1(ΔE9)), and APPSL/PSEN1(ΔE9) with GFP or mCherry as a reporter for viral infection (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, human neurons were differentiated from the ReNcell VM progenitor cell line (38) and treated with glutamate in the absence or presence of NDP-MSH. Similar to murine cells, human neurons expressed MC1R and up-regulated NR4A1 on mRNA and protein level in response to NDP-MSH (Fig.…”
Section: Ndp-msh Protected Human Neuronal Cells From Glutamate-inducementioning
confidence: 99%